2009
DOI: 10.5380/rsa.v10i4.14801
|View full text |Cite
|
Sign up to set email alerts
|

Período Anterior a Interferência De Plantas Daninhas Em Soja Transgênica

Abstract: RESUMOO presente trabalho foi conduzido com o objetivo de se determinar o período anterior à interferência das plantas daninhas com a cultura da soja, cv. Monsoy 7908 RR plantada no sistema convencional. Os períodos de convivência estudados foram: 0, 10, 15, 20, 30, 40, 50, 60 e 118 dias após a emergência, totalizando 10 tratamentos, que foram dispostos em blocos casualizados, com quatro repetições. A comunidade infestante foi composta por 20 espécies, com Alternanthera tenella, Digitaria nuda e Eleusine indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…There was a greater predominance of families of dicotyledonous plants (88%) than monocotyledons (22%) in population weed species (Table 1). The weed families found in this study resemble those identified in the soybean crop (Benedetti et al, 2009), cassava (Marques et al, 2010;Cardoso et al, 2013) and coffee (Maciel et al, 2010). The first three authors reported that the Asteraceae family was the owner of a large number of species.…”
Section: Resultssupporting
confidence: 67%
“…There was a greater predominance of families of dicotyledonous plants (88%) than monocotyledons (22%) in population weed species (Table 1). The weed families found in this study resemble those identified in the soybean crop (Benedetti et al, 2009), cassava (Marques et al, 2010;Cardoso et al, 2013) and coffee (Maciel et al, 2010). The first three authors reported that the Asteraceae family was the owner of a large number of species.…”
Section: Resultssupporting
confidence: 67%
“…The weed interference in soybean during all the crop cycle reduces yield 73 to 94% in different sowing times (Zandona, et al, 2018). Considering a 5% tolerable yield decline, the soybean crop was negatively affected by weed infestation starting at 25 DAE (PAI) (Benedetti et al, 2009). The inefficient poaceous weed control provided by the control without herbicide and resulting increase in weed interference with the soybean crop caused a significant decrease in seed yield (600 to 1400 kg ha -1 ) (Purí ssimo, 2002).…”
Section: Soybean Yieldmentioning
confidence: 99%
“…Goosegrass (Eleusine indica) infests several crops and may cause irreversible damage on yield, specially when competing in the initial stages of the crops (Benedetti et al, 2009). Worldwide, this weed has 29 cases of resistance belonging to seven mechanisms of action, with 11 cases of resistance to glyphosate being reported.…”
Section: Introductionmentioning
confidence: 99%